Leukocyte Differentiation Mice (Mus Musculus) Infected with Plasmodium Berghei after Therapy With Sargassum Duplicatum Extract - Abdul M Ukratalo; Suyono Lateke (Nusantara Scientific Medical, 2023)
Leukocytes are white blood cells produced by hematopoietic tissue that serves to help the body fight various infectious diseases as part of the immune system. Sargassum duplicatum contains steroid, alkaloid, phenol, flavonoid, saponin, and tannin compounds that can be immunomodulatory. The purpose of this research is to know the effect of methane extract of brown algae Sargassum duplicatum on the differentiation of leukocyte mice (Mus musculus) infected with Plasmodium berghei. Mice weighing 20-30 grams in Plasmodium berghei infection as much as 0.1 ml per head and left to the percentage of parasitemia reaches 1-5%. Then the mice (Mus musculus) were given brown algae methanol extract (Sargassum duplicatum) at doses 10, 100, and 200 mg / g BW for 4 consecutive days. From day 0 to 6 also made a blood smear to calculate the number of leukocytes. Data analysis will be done using ANOVA. The results showed that the administration of brown algae extracts of Sargassum duplicatum influenced in increasing the number of neutrophils, monocytes, and basophils and decreased the number of eosinophils and lymphocytes of mice infected with Plasmodium berghei to near normal range. Dose 200 mg/kg BB methanol extract of brown alga Sargassum duplicatum is a dose that can affect the number of neutrophils, eosinophils, lymphocytes, and monocytes of mice infected with Plasmodium berghei most closely to normal range.